What I Heard About Manus Island (When I Listened to 14 Hours of Recordings from Manus Island) - André Dao (Law Text Culture, 2020)
This essay stages a hearing of the first seven recordings (the first 70 minutes, or the first week) of how are you today, an artwork produced by six men detained by the Australian Government on Manus Island, and three collaborators based in Melbourne (together, the Manus Recording Project Collective). In this staging, conducted by one of the Melbourne based collaborators, ‘hearing’ shifts between the sonic and the metaphoric, and between the ear and the mind. The hearing is concerned with the question: what is the nature of the relation between the hearer and the one whose hearing is heard?